2011
DOI: 10.1016/j.expneurol.2011.08.012
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box-1 impairs memory in mice through both toll-like receptor 4 and Receptor for Advanced Glycation End Products

Abstract: High-mobility group box-1 (HMGB1) is a nuclear protein with cytokine-type functions upon its extracellular release. HMGB1 activates inflammatory pathways by stimulating multiple receptors, chiefly toll-like receptor 4 (TLR4) and Receptor for Advanced Glycation End Products (RAGE). TLR4 and RAGE activation has been implicated in memory impairments, although the endogenous ligand subserving these effects is unknown. We examined whether HMGB1 induced memory deficits using novel object recognition test, and which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(110 citation statements)
references
References 63 publications
(84 reference statements)
4
103
0
Order By: Relevance
“…It showed potent antiinflammatory and neuroprotective effects in spinal cord cultures, significantly counteracting the effects of TLR4 stimulation by LPS (that is, microglial morphological changes and release of proinflammatory cytokines and motor neuron toxicity). The effects of VB3323 were comparable to those of a wellknown, commercially available TLR4 antagonist, the LPS from RsLPS, which is commonly used to inhibit the TLR4-dependent inflammatory mechanisms (45)(46)(47).…”
Section: Discussionmentioning
confidence: 68%
“…It showed potent antiinflammatory and neuroprotective effects in spinal cord cultures, significantly counteracting the effects of TLR4 stimulation by LPS (that is, microglial morphological changes and release of proinflammatory cytokines and motor neuron toxicity). The effects of VB3323 were comparable to those of a wellknown, commercially available TLR4 antagonist, the LPS from RsLPS, which is commonly used to inhibit the TLR4-dependent inflammatory mechanisms (45)(46)(47).…”
Section: Discussionmentioning
confidence: 68%
“…Further support for a role of RAGE in modulating synaptic activity was provided by Sakatani et al (2007); these authors revealed that kainate-induced seizures in S100 À/À mice were weaker than in wild type controls, and that this effect was mediated by RAGE-S100 interactions. More recently, a series of reports linking RAGE activation and NMDA receptor function aimed to explain the detrimental effects of RAGE on memory (Mazarati et al, 2011). For example, activation of RAGE by HMGB1 impairs memory encoding in mice independently of the known HMGB1 binding to toll-like receptor 4 (TLR4) (Mazarati et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…S100-induced modifications of intracellular Ca 2+ in astrocytes (Barger and Van Eldik, 1992) and in neurons by activation of RAGE receptors (Huttunen et al, 2000) appear to be involved in the modulation of synaptic plasticity. S100β released by astrocytes may also promotes changes in neuronal rhythms that are relevant for seizure onset (Morquette et al, 2015;Sakatani et al, 2008), and RAGE receptors areimplicated in both cognitive impairments (Mazarati et al, 2011) and epileptogenesis (Iori et al, 2013). In this context, there is increasing evidence that activated astrocytes play a key role in neuronal network hyperexcitability underlying seizures (Devinsky et al, 2013;Robel et al, 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%